APPLICATION OF THE PROJECT-BASED LEARNING MODEL IN THE PUB (FASHION BUSINESS MANAGEMENT) COURSE TO ENHANCE STUDENT CREATIVITY - Tri Mutmainnah; Marniati Marniati; Mein Karnolis (Yayasan Amanah Nur Aman, 2026)
This study aims to enhance students’ creativity in the Pengelolaan Usaha Busana (PUB/Fashion Business Management) course through the implementation of the Project-Based Learning (PjBL) model. The research employed a Classroom Action Research design conducted in two cycles. The subjects of this study were 100 students from the 2024 cohort of the Fashion Education Study Program. Data were collected through observation, questionnaires, interviews, and project assessment. The data were analyzed descriptively using quantitative approaches by calculating the percentage of creativity improvement in cognitive, affective, and psychomotor aspects. The results show that the application of the Project-Based Learning model successfully improved student creativity. Psychomotor creativity increased from 58.12% in the pre-cycle to 69.45% in Cycle I and 82.23% in Cycle II. Affective creativity increased from 56.75% to 65.48% and 79.86%, while cognitive creativity increased from 60.28% to 70.14% and 84.32%. These findings indicate that Project-Based Learning is effective in improving students’ creativity in project-based learning within the PUB course.